2016
DOI: 10.1371/journal.pone.0153775
|View full text |Cite|
|
Sign up to set email alerts
|

“I Can Remember Sort of Vivid People…but to Me They Were Plasticine.” Delusions on the Intensive Care Unit: What Do Patients Think Is Going On?

Abstract: IntroductionPatients who develop intensive care unit (ICU) acquired delirium stay longer in the ICU, and hospital, and are at risk of long-term mental and physical health problems. Despite guidelines for patient assessment, risk limitation, and treatment in the ICU population, delirium and associated delusions remain a relatively common occurrence on the ICU. There is considerable information in the literature describing the incidence, suspected causes of, and discussion of the benefits and side-effects of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 70 publications
0
20
0
4
Order By: Relevance
“…It was also evident that current participants desired to be oriented not only to the interventions but also to what was happening in their surroundings. The importance of early patients' psychological intervention in the form of repeated orientation whilst in the ICU has been documented (Darbyshire et al ., ). Reported by Meuter et al .…”
Section: Discussionmentioning
confidence: 97%
“…It was also evident that current participants desired to be oriented not only to the interventions but also to what was happening in their surroundings. The importance of early patients' psychological intervention in the form of repeated orientation whilst in the ICU has been documented (Darbyshire et al ., ). Reported by Meuter et al .…”
Section: Discussionmentioning
confidence: 97%
“…Respecto a los factores de riesgo, se destaca: Edad avanzada, tabaquismo (Yang et al, 2017), alcoholismo, que si bien la asociación aún no es clara, puede extenderse más allá de la abstinencia alcoholica, puede estar relacionado a deficiencias nutricionales o tener un marcador desconocido para el desarrollo del delirio (Wood et al, 2017), actividad física baja, bajo índice de masa corporal (<18,6 kg/m2), discapacidad auditiva, fibrilación auricular, antecedentes de accidente cerebrovascular, insuficiencia renal crónica, trastornos del sueño, depresión, antecedentes de delirio, medicación con benzodiazepinas, medicamentos neurolépticos, analgésicos opioides y múltiples medicamentos, polifarmacia, la cual se asocia con aumento de los eventos adversos, mayor interacción de los medicamentos y aumento de los costos (Garpestad y Devlin, 2017), la infección al torrente sanguíneo, inserción de catéteres y drenajes (Dittrich et al, 2016) y finalmente, el adormecimiento o somnolencia identificado con un RASS -1 (Boettger et al, 2017). Por otra parte, los factores precipitantes del delirio fueron la cirugía de emergencia, cirugía abierta, los catéteres permanentes múltiples, uso de analgésicos opioides y benzodiazepinas, la admisión a la unidad de cuidados intensivos (UCI), el ingreso a la sala de emergencias (Kim et al, 2016;Mori et al, 2016), puntaje SOFA (≥14) (Yang et al, 2017), y el delirio hiperactivo genera estancias más cortas y una menor mortalidad hospitalaria.…”
Section: Resultados E Interpretaciónunclassified
“…Participants in the study reported high levels of fear, using terms such as ‘terrifying’ and ‘scared’, emotions that are associated with aggressive behaviour (Brooke & Manneh ) Reduced sense of personal autonomy has also been associated with the aggressive behaviours sometimes observed in people with delirium (Darbyshire et al . ; Fagerberg & Jönhagen ). Understanding these emotions provides nurses with opportunities for intervention, including building trust, reorientation, and promoting a safe environment with predictable stimuli.…”
Section: Discussionmentioning
confidence: 99%